Oscillatory activity and cortical coherence of the nucleus basalis of Meynert in Parkinson's disease dementia. (July 2018) - Nazmuddin, Muhammad; Oterdoom, D.L.Marinus; van Dijk, J. Marc C.; van Zijl, Jonathan C.; Kampman, Anne K.; Drost, Gea; van Laar, Teus; Beudel, Martijn
Abstract: Background: Deep brain stimulation (DBS) of the nucleus basalis of Meynert (NBM) is a new potential treatment for Parkinson's Disease dementia (PDD) and other types of dementia. To get a better understanding of this structure, its local neurophysiological properties and cortical connectivity patterns were studied. Methods: We simultaneously recorded DBS local field potentials (LFPs) and electroencephalography (EEG) in two patients with PDD. Both patients had DBS electrodes in the internal globus pallidus (GPi) with one or more distal contacts close to or inside the NBM. Measurements were obtained during routine battery replacement. The distance of DBS contacts to the NBM were calculated using CT-MRI fusion. Results: Delta (1–4 Hz) oscillations were more prominently present in the NBM region than in its vicinity, whereas temporal coherence in the theta (4–8 Hz) range was less outspoken. Conclusion: These neurophysiological characteristics, if also proven in larger cohorts, might help to map the NBM more precisely during electrode implantation. Highlights: DBS battery placement enables the recording of neural activity in cholinergic nuclei. Local field potential (LFP) by DBS contacts in and outside the basal nucleus (NBM) are described. The cortical coherence of LFPs recorded from DBS electrodes in and outside the NBM are described.